Preparation method and application of high-performance silicon-based thin film
By using a porous structure silicon-oxygen composite film as the negative electrode material in lithium-ion batteries, the problem of falling off due to volume expansion of silicon electrodes is solved, the cycle performance and first charge and discharge efficiency of the battery are improved, and it is suitable for industrial production.
Patent Information
- Application Number
- CN202411327858.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-17
AI Technical Summary
The negative electrode material of lithium-ion battery, silicon, during the charging and discharging process, causes the electrode to fall off from the current collector, and the circulation performance decreases, and the conductivity of silicon is poor, affecting the electrochemical performance.
Using the preparation method of porous structure silicon-oxygen composite film, the silicon-oxygen composite film is sputtered in a mixed atmosphere of inert gas and oxygen, and annealing and hydrofluoric acid etching, forming a larger specific surface area and small interface resistance. The porous structure silicon-oxygen composite film, as the negative electrode material of the electrode sheet, absorbs volume expansion and reduces the generation of solid electrolyte film.
It improves the circulation performance and first charge and discharge efficiency of lithium-ion batteries, extends battery life, reduces internal resistance, enhances safety performance, and is suitable for industrial production.
Smart Images

Figure CN119144927A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of chemical power sources, and in particular relates to a porous silicon-oxygen composite film and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries have been widely used in 3C electronic products (Computer, Consumer Electronic and Communication), energy storage equipment, electric vehicles and marine fields due to their significant advantages such as high energy density, high operating voltage, long cycle life, low self-discharge and environmental friendliness. The energy density of lithium-ion batteries is about 3 to 4 times that of traditional lead-acid batteries, making them very attractive in the field of power supply. The energy density of the negative electrode material is one of the main factors affecting the energy density of lithium-ion batteries. It can be seen that the negative electrode material plays a vital role in the lithium-ion battery chemical system. Silicon-based lithium-ion battery negative electrode material is one of the most widely studied materials.
[0003] Silicon is a hot material for negative electrodes of lithium-ion batteries mainly because it can form Li4Si alloy with lithium, with a theoretical lithium storage capacity of up to 4200mAh / g (more than 10 times the capacity of graphite); the lithium insertion potential of silicon (0.5V) is slightly higher than that of graphite, and it is difficult to form "lithium dendrites" during charging; silicon has low reactivity with electrolytes and will not co-intercalate with organic solvents. However, silicon electrodes will experience reduced cycle performance and capacity decay during the charge and discharge process. When silicon and lithium form Li4Si alloy, the volume expands by up to 320%. The huge volume change can easily cause the active material to fall off from the current collector, thereby reducing the electrical contact with the current collector, causing the electrode cycle performance to decline rapidly. Compared with silicon, silicon-oxygen composite materials have smaller volume expansion and better cycle performance, but they cannot meet the needs of industrialization. Summary of the invention
[0004] The purpose of the present invention is to overcome the above-mentioned deficiencies of the prior art and to provide a porous structured silicon-oxygen composite film and a preparation method thereof, so as to solve the problem that the existing silicon-oxygen composite film as a negative electrode material expands in volume during charging and discharging, thereby causing the film to fall off the current collector.
[0005] Another object of the present invention is to provide an electrode sheet and an application of the electrode sheet to solve the technical problem that the existing silicon-containing electrode sheets have unsatisfactory electrochemical properties, such as poor electrical conductivity due to silicon itself being a semiconductor material.
[0006] In order to achieve the purpose of the present invention, one aspect of the present invention provides a method for preparing a porous silicon-oxygen composite film. The method for preparing a porous silicon-oxygen composite film comprises the following steps: The silicon target is sputtered in a mixed atmosphere of inert gas and oxygen, a silicon-oxygen composite film is grown on a substrate, and annealing is performed to obtain a composite film of silicon and silicon oxide; the silicon-oxygen composite film is then etched with hydrofluoric acid, and after cleaning and drying, a porous silicon-oxygen composite film is obtained.
[0007] Another aspect of the present invention provides a porous silicon-oxygen composite film, which is grown by the method for preparing the porous silicon-oxygen composite film of the present invention.
[0008] Another aspect of the present invention provides an electrode sheet, which includes a current collector, and a porous silicon-oxygen composite film is bonded to the surface of the current collector, wherein the porous silicon-oxygen composite film is grown on the current collector according to the preparation method of the present invention.
[0009] Another aspect of the present invention provides the use of the electrode sheet of the present invention, which is used in the preparation of lithium-ion batteries or supercapacitors.
[0010] Compared with the prior art, the porous structure silicon oxygen composite film of the present invention is to sputter the silicon target in a mixed atmosphere of inert gas and oxygen, and anneal to obtain a composite film of silicon and silicon oxide; then the silicon oxygen composite film is etched with hydrofluoric acid, cleaned and dried to form. In this way, the silicon oxygen compound in the film is etched by hydrofluoric acid, thereby forming a larger specific surface area in the silicon oxygen composite film for lithium ions to accommodate, giving the porous structure silicon oxygen composite film the characteristic of small interface resistance. Moreover, after the porous structure silicon oxygen composite film is used as a negative electrode film layer, it can also absorb the volume expansion generated by the silicon oxygen composite during charging and discharging, reduce the stress of periodic volume changes, reduce the generation of solid electrolyte membrane (SEI), and maintain the structural stability during the lithium ion embedding / ejection process. In addition, the film layer is grown and formed by radio frequency magnetron sputtering, and its conditions are easy to control, which effectively ensures that the chemical properties of the grown porous structure silicon oxygen composite film are stable, giving the porous structure silicon oxygen composite film good high rate performance, good safety performance, high efficiency, and suitable for industrial large-scale production.
[0011] Therefore, the porous structure of the silicon-oxygen composite film of the present invention has a small interface resistance, can absorb the volume expansion of the silicon-oxygen composite during charging and discharging, reduce the stress of periodic volume changes, reduce the generation of solid electrolyte membrane (SEI), and maintain structural stability during lithium ion insertion / extraction.
[0012] The electrode sheet of the present invention is formed by growing a silicon-oxygen composite film on a current collector using the preparation method of the present invention, and then forming a porous silicon-oxygen composite film by etching with hydrofluoric acid. Therefore, the electrode sheet has a small internal resistance, and the porous silicon-oxygen composite film contained therein can absorb the volume expansion generated by the silicon-oxygen composite during charging and discharging, reduce the stress of periodic volume changes, reduce the generation of solid electrolyte membrane (SEI), and maintain the structural stability during the lithium ion embedding / ejection process. In addition, the preparation method is simple in process, low in equipment dependence, and suitable for industrial production. The composite film prepared by the method has a high specific capacity and good structural stability.
[0013] Due to the advantages of the electrode sheet of the present invention, the lithium ion conduction rate of the lithium ion battery containing the electrode sheet of the present invention is high, the structural stability and the capacity retention rate are high, the lithium ion battery is endowed with high initial charge and discharge efficiency and good cycle performance of the lithium ion battery or supercapacitor, the cycle life is extended, and the safety performance is high. The supercapacitor containing the electrode sheet of the present invention has a small internal resistance, fast charge and discharge, and excellent energy storage performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 A comparison diagram of the charge and discharge curves of a lithium-ion battery of the thin film electrode material provided by Example 6 of the present invention and Comparative Example 2 at 150 mA / g; Figure 2 The charge and discharge curves of the lithium-ion battery containing the porous silicon-oxygen composite film electrode material provided in Example 6 of the present invention at 150 mA / g for the first cycle, the 50th cycle, and the 100th cycle; Figure 3 It is a comparison diagram of the first charge and discharge curves of lithium ion batteries containing porous structure silicon oxygen composite thin film electrode materials provided by Examples 7, 8, 9 and 10 of the present invention at 150 mA / g; wherein, curve 1 is the first charge and discharge curve of the lithium ion battery obtained in Example 7, curve 2 is the first charge and discharge curve of the porous structure silicon oxygen composite thin film electrode material obtained in Example 8, curve 3 is the first charge and discharge curve of the lithium ion battery obtained in Example 9, and curve 4 is the first charge and discharge curve of the lithium ion battery obtained in Example 10; Figure 4 is a comparison chart of the cycle performance of the lithium ion battery obtained in Example 6 of the present invention and in Comparative Example 2 at 3000 mA / g; Figure 5 This is a graph of the cycle retention rate of a lithium-ion battery containing a porous silicon-oxygen composite thin film electrode material at 3000 mA / g obtained in Example 6 of the present invention. DETAILED DESCRIPTION Embodiment 1
[0015] This embodiment provides a porous silicon-oxygen composite film and a preparation method thereof. The porous silicon-oxygen composite film is prepared according to a method comprising the following steps: S11: A single crystal silicon wafer with a (100) crystal plane was used as the sputtering source, and the target-substrate distance was 80 mm on a copper foil; a composite film of silicon and silicon oxide with a thickness of 1 μm was prepared by radio frequency magnetron sputtering in a mixed atmosphere of high-purity argon and oxygen with an argon-oxygen ratio of 4:1 at 1.0×10-2 mbar. During deposition, the substrate was kept at 300°C.
[0016] S12: annealing the composite thin film of silicon and silicon oxide prepared in step S11 in an oxygen atmosphere at an annealing temperature of 300° C. for 30 minutes, thereby obtaining an annealed composite thin film of silicon and silicon oxide.
[0017] S13: Add hydrofluoric acid dropwise onto the annealed silicon and silicon oxide composite film obtained in step S12, react for 30 minutes, wash with deionized water, and place in a vacuum drying oven at 80°C for 12 hours to prepare a porous silicon-oxygen composite film after hydrofluoric acid etching. Embodiment 2
[0018] This embodiment provides a porous silicon-oxygen composite film and a preparation method thereof. The porous silicon-oxygen composite film is prepared according to a method comprising the following steps: S11: Using a single crystal silicon wafer with a (100) crystal plane as the sputtering source, on a copper foil, with a target-substrate distance of 60 mm, in a mixed atmosphere of high-purity argon and oxygen with a ratio of argon to oxygen of 6:1 at 1.0×10-2 mbar, a composite film of silicon and silicon oxide with a thickness of 0.5 μm was prepared by radio frequency magnetron sputtering. During deposition, the substrate was kept at 500°C.
[0019] S12: annealing the composite thin film of silicon and silicon oxide prepared in step S11 in an oxygen atmosphere at an annealing temperature of 300° C. for 60 minutes, thereby obtaining an annealed composite thin film of silicon and silicon oxide.
[0020] S13: Add hydrofluoric acid dropwise onto the annealed silicon and silicon oxide composite film obtained in step S12, react for 60 minutes, wash with deionized water, and place in a vacuum drying oven at 80°C for 12 hours to prepare a porous silicon-oxygen composite film etched with hydrofluoric acid. Embodiment 3
[0021] This embodiment provides a porous silicon-oxygen composite film and a preparation method thereof. The porous silicon-oxygen composite film is prepared according to a method comprising the following steps: S11: Using a single crystal silicon wafer with a (100) crystal plane as the sputtering source, on a Japanese 304 stainless steel substrate, with a target-substrate distance of 80 mm, in a mixed atmosphere of high-purity argon and oxygen with a ratio of argon to oxygen of 4:1 at 1.0×10-2 mbar, a composite film of silicon and silicon oxide with a thickness of 1 μm was prepared by radio frequency magnetron sputtering. During the deposition, the substrate was kept at 300°C.
[0022] S12: annealing the composite thin film of silicon and silicon oxide prepared in step S11 in an oxygen atmosphere at an annealing temperature of 300° C. for 30 minutes, thereby obtaining an annealed composite thin film of silicon and silicon oxide.
[0023] S13: Add hydrofluoric acid dropwise onto the annealed silicon and silicon oxide composite film obtained in step S12, react for 15 minutes, wash with deionized water, and place in a vacuum drying oven at 80° C. for 12 hours to prepare a porous silicon-oxygen composite film after hydrofluoric acid etching. Embodiment 4
[0024] This embodiment provides a porous silicon-oxygen composite film and a preparation method thereof. The porous silicon-oxygen composite film is prepared according to a method comprising the following steps: S11: Using a single crystal silicon wafer with a (100) crystal plane as the sputtering source, on a copper foil, with a target-substrate distance of 80 mm, in a mixed atmosphere of high-purity argon and oxygen with a ratio of argon to oxygen of 2:1 at 1.0×10-2 mbar, a composite film of silicon and silicon oxide with a thickness of 0.2 μm was prepared by radio frequency magnetron sputtering. During deposition, the substrate was kept at 300°C.
[0025] S12: annealing the composite thin film of silicon and silicon oxide prepared in step S11 in an air atmosphere at an annealing temperature of 100° C. for 30 minutes, thereby obtaining an annealed composite thin film of silicon and silicon oxide.
[0026] S13: Add hydrofluoric acid dropwise onto the annealed silicon and silicon oxide composite film obtained in step S12, react for 15 minutes, wash with deionized water, and place in a vacuum drying oven at 80° C. for 12 hours to prepare a porous silicon-oxygen composite film after hydrofluoric acid etching. Embodiment 5
[0027] This embodiment provides a porous silicon-oxygen composite film and a preparation method thereof. The porous silicon-oxygen composite film is prepared according to a method comprising the following steps: S11: Using a single crystal silicon wafer with a (100) crystal plane as the sputtering source, on a copper foil, with a target-substrate distance of 80 mm, in a mixed atmosphere of high-purity argon and oxygen with a ratio of argon to oxygen of 4:1 at 1.0×10-2 mbar, a composite film of silicon and silicon oxide with a thickness of 1 μm was prepared by radio frequency magnetron sputtering. During the deposition, the substrate was kept at 300°C.
[0028] S12: annealing the composite thin film of silicon and silicon oxide prepared in step S11 in an air atmosphere at an annealing temperature of 100° C. for 15 minutes, thereby obtaining an annealed composite thin film of silicon and silicon oxide.
[0029] S13: Add the hydrofluoric acid and nitric acid mixed solution dropwise onto the annealed silicon and silicon oxide composite film obtained in step S12, react for 15 minutes, wash with deionized water, and place in a vacuum drying oven at 80°C for 12 hours to prepare a porous structure silicon-oxygen composite film after hydrofluoric acid etching.
[0030] Comparative Example 1 This embodiment provides a silicon-oxygen composite film and a method for preparing the same. The silicon-oxygen composite film is prepared according to a method comprising the following steps: S11: Using a single crystal silicon wafer with a (100) crystal plane as the sputtering source, on a copper foil, with a target-substrate distance of 80 mm, in a mixed atmosphere of high-purity argon and oxygen with a ratio of argon to oxygen of 4:1 at 1.0×10-2 mbar, a composite film of silicon and silicon oxide with a thickness of 0.1 μm was prepared by radio frequency magnetron sputtering. During deposition, the substrate was kept at 300°C.
[0031] Examples 5 to 10 and Comparative Example 2 The copper foil substrate containing the porous silicon-oxygen composite film provided in each of the above-mentioned embodiments 1 to 5 is used as the negative electrode, and the copper foil containing the silicon-oxygen composite film provided in the comparative example 1 is used as the negative electrode, and lithium-ion batteries are assembled according to the following methods: A button cell was assembled in an argon-filled glove box using lithium sheets as thin film electrodes, an electrolyte concentration of 1 mol / L, and a polypropylene microporous membrane as a battery separator.
[0032] Each lithium-ion battery was subjected to the following relevant electrochemical test conditions: the charge and discharge voltage was 0.01V to 3V.
[0033] Relevant electrochemical test results of each lithium-ion battery: The lithium ion battery provided in Example 6 has an initial discharge capacity of 2906mah / g and a charge capacity of 2686mah / g at a rate of 150mA / g. Figure 1Furthermore, the charge and discharge curves of the lithium-ion battery provided in the seventh embodiment at 150 mA / g for the first cycle, the 50th cycle, and the 100th cycle are as shown in FIG. Figure 2 The cycle performance curve at 3000mA / g is shown in Figure 4 As shown, the Coulomb efficiency curve at 3000mA / g is as follows Figure 5 shown.
[0034] The lithium ion battery provided in Example 7 has an initial charge capacity of 2659 mAh / g and a discharge capacity of 2877 mAh / g at a rate of 150 mA / g.
[0035] The lithium ion battery provided in Example 8 has an initial charge specific capacity of 2716 mAh / g and a discharge specific capacity of 2872 mAh / g at a rate of 150 mAh / g.
[0036] The lithium ion battery provided in Example 9 has an initial charge specific capacity of 2450 mA / g and a discharge specific capacity of 2651 mA / g at a rate of 150 mA / g.
[0037] The lithium ion battery provided in Example 10 has an initial charge specific capacity of 2716 mA / g and a discharge specific capacity of 2788 mA / g at a rate of 150 mA / g.
[0038] The lithium ion battery provided in Comparative Example 2 has an initial charge capacity of 2508 mA / g and a discharge capacity of 2886 mA / g at a rate of 150 mA / g. Figure 1 shown.
[0039] In addition, the first charge and discharge curve comparison curve of the lithium ion battery provided in Examples 6 to 10 at 150 mA / g is as follows: Figure 3 shown.
[0040] Comparing the charge and discharge performance of the lithium-ion batteries provided in Examples 6 to 10 and the lithium-ion batteries provided in Comparative Example 2, it can be seen that the lithium-ion batteries containing the porous silicon-oxygen composite thin films provided in Examples 1 to 5 are significantly better than the lithium-ion batteries with composite thin film negative electrodes of silicon and silicon oxide. Therefore, the electrochemical test results of each lithium-ion battery show that the lithium-ion battery has high initial charge and discharge efficiency and good cycle performance, and stable charge and discharge performance.
[0041] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a porous silicon-oxygen composite film, characterized in that: The steps include: The silicon target is sputtered in a mixed atmosphere of inert gas and oxygen, a silicon-oxygen composite film is grown on a substrate, and annealing is performed to obtain a composite film of silicon and silicon oxide; the silicon-oxygen composite film is then etched with a corrosive agent, and after cleaning and drying, a porous silicon-oxygen composite film is obtained.
2. The preparation method according to claim 1, characterized in that: The corrosive agent includes one or more of hydrofluoric acid, nitric acid, hydrochloric acid, aqua regia and the like; and / or The etching treatment conditions are: the concentration of the corrosive agent is 5wt% to 60wt%, the etching method includes one or more of dropwise addition, immersion, etc., and the etching time is 2min to 240min; and / or The sputtering power and sputtering time of the sputtering treatment meet the following conditions: the power of sputtering the silicon target material is 20W to 200W, and the time is 30min to 300min.
3. The preparation method according to claim 1, characterized in that: During the sputtering process, the temperature of the substrate is controlled to be 10°C-800°C; The sputtering atmosphere is a mixed atmosphere of at least one or more of nitrogen and argon and oxygen; the mixing ratio of the sputtering atmosphere to the oxygen atmosphere is 8:1 to 1:
1.
4. The preparation method according to any one of claims 1 to 3, characterized in that: The silicon target material is a pressed target material of a single crystal silicon wafer or silicon powder.
5. The preparation method according to any one of claims 1 to 3, characterized in that: The substrate is a negative electrode current collector of a chemical power source.
6. A porous silicon-oxygen composite film, characterized in that: The porous silicon-oxygen composite film is grown according to the preparation method described in any one of claims 1-5.
7. An electrode sheet, comprising a current collector, characterized in that: A porous silicon-oxygen composite film is also combined on the surface of the current collector. The porous silicon-oxygen composite film is grown on the current collector according to the preparation method according to any one of claims 1 to 5.
8. The electrode sheet according to claim 7, characterized in that: The thickness of the porous silicon-oxygen composite film is 0.1-10 μm.
9. Use of the electrode sheet as claimed in claim 7 or 8 in a lithium ion battery or a supercapacitor.
